(untitled) - Walles, Brenda (Netherlands, 2015)
The role of ecosystem engineers in the ecomorphological development of intertidal habitats: General introduction & outline of the thesis; The ecosystem engineer Crassostrea gigas affects tidal flat morphology beyond the boundary of their reef structures,...
Keywords: Sinh thái liên triều,Intertidal ecology